PENGARUH PENGGUNAAN METODE BLENDED LEARNING TERHADAP HASIL BELAJAR DENGAN VARIABEL MODERATOR KECERDASAN SISWA - Een Ernawati; Iskandar Iskandar; Yeyen Suryani (Universitas Kuningan, 2022)
Abstract The impact of the COVID-19 pandemic has caused SMK Negeri 3 Kuningan to implement an online learning pattern. The implementation of the online process, which is still in the process of adjustment, has a tremendous impact on student learning outcomes. The results of the assessment of students at the XI level of the subject (Creative Entrepreneurship Products) have not shown unsatisfactory results. The low learning outcomes of students are due to several factors. Such as the use of learning methods that are not appropriate, the low carrying capacity of student learning, due to the economic status of the family and the level of intelligence of students.This research of the purpose is to describe the differences at student of learning outcomes used Blended Learning and expository method to students, to describe the high differences outcomes in student learning intelligence levels and students with low intelligence levels or to describe the interaction between the learning model or the level of intelligence. The student outcomes at influencing of the intelligence at SMK Negeri 3 Kuningan. The research method uses a quasi-experimental design.The student are class XI MM 1 of as subject the research at SMK Negeri 3 Kuningan in the 2020-2021 school year, as many as 37 people. The techniques data collections using pretest and postest and intelligence questionnaire. The technique data analysis used descriptive analysis. The technique used two ways ANOVA at the hypothesis testing.There were differences showed that in student learning outcomes using the Blended Learning model using the lecture method after the Tests of Between Subjects Effects were carried out and an interaction between the Blended Learning model and the level of student intelligence in influencing student learning outcomes after the influence test (F test) is carried out. Based on the results of the study, the authors provide the following suggestions: Given that the blended learning method is positively correlated with student learning outcomes, it is hoped that the blended learning method can be applied in learning, especially after the Covid 19 pandemic outbreak which requires adaptation and adjustment of the learning process; Given that there is a positive correlation between the level of intelligence of students and student learning outcomes, it is necessary to carry out a test of the level of intelligence of students in schools. It is intended that the learning process can be carried out as well as possible by adjusting to the level of student intelligence; efforts need to be made to provide a good learning environment for students so that each student can bring out his full potential. There is a need for further studies on this research in the future. Keywords : Blended learning; students intelligence; learning outcome Abstrak Dampak dari pandemi covid 19, menyebabkan SMK Negeri 3 Kuningan harus menerapkan pola belajar daring. Pelaksanaan proses daring yang masih dalam proses penyesuaian-penyesuaian mengakibatkan dampak yang luar biasa terhadap hasil belajar siswa. Hasil penilaian peserta didik ditingkat XI mapel (Produk Kreatif Kewirausahaan) belum menunjukkan hasil yang belum memuaskan, rendahnya hasil belajar siswa dikarenakan beberapa faktor. Seperti pemakaian metode belajar yang belum tepat, rendahnya daya dukung belajar siswa, karena status ekonomi keluarga dan tingkat kecerdasan siswa. Penelitian ini bertujuan untuk mendeskripsikan perbedaaan hasil belajar siswa dalam penggunaan Metode Blended Learning dibandingkan metode ceramah pada siswa, untuk mendeskripsikan pengaruh tingkat kecerdasan emosional siswa terhadap hasil belajar siswa dan untuk mendeskripsikan hubungan metode pembelajaran dengan tingkat kecerdasan emosional siswa dalam mempengaruhi hasil belajar siswa pada SMK Negeri 3 Kuningan. Metode penelitan menggunakan desain quasi eksperimental. Subyek penelitan adalah siswa kelas XI MM 1 SMK Negeri 3 Kuningan TP 2020 -2021, berjumlah 37 orang. Dalam mengumpulkan data dengan menggunakan teknik yaitu pre test-post test dan angket kecerdasan. Untuk menganalisis data digunakan tehnik analisis deskriptif.Dalam menguji hipotesis digunakan rumus two ways anova .Setelah melakukan penelitian didapat hasil yang menunjukkan yaitu terdapat pengaruh yang signifikan dengan penggunaan metode Blended Learning dibandingkan metode ceramah setelah dilakukan Tests of Between Subjects Effects, terdapat perbedaan hasil belajar siswa berdasarkan tingkat kecerdasan emosional siswa setelah dilaksanakan Tests of Between Subjects Effects, dan adanya hubungan antara metode Blended Learning dan tingkat kecerdasan emosional siswa sehingga memberikan pengaruh pada hasil belajar siswa setelah dilaksanakan uji pengaruh (uji F). Berdasarkan hasil penelitian, maka penulis memberikan saran-saran sebagai berikut ;Mengingat metode pembelajaran blended learning berkorelasi positif terhadap hasil belajar siswa maka diharapkan metode pembelajarn blended learning dapat diaplikasi dalam pembelajaran terutama setelah adanya wabah pandemi Covid 19 yang menuntut adanya adaptasi dan penyesuaian proses pembelajaran. Mengingat terdapat korelasi positif antara tingkat kecerdasan siswa dengan hasil belajar siswa maka perlu adanya pelaksanaan test tingkat kecerdasan siswa dilaksanakan di sekolah. Hal ini bertujuan agar proses pembelajaran dapat dilaksanakan sebaik mungkin dengan menyesuaikan pada tingkat kecerdasan siswa; Perlu adanya upaya memberikan lingkungan belajar yang baik bagi siswa agar setiap siswa dapat mengeluarkan seluruh potensinya. Perlu adanya kajian lebih lanjut atas penelitian ini dimasa yang akan datang. Kata kunci : Blended learning; kecerdasan siswa; hasil belajar